2018
DOI: 10.15587/1729-4061.2018.144553
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the structure and sorption peculiarities of cobalt and uranium ions by nanocomposites based on montmorillonite and tetraethoxysilane

Abstract: 6 organisms. One of the most dangerous heavy metals and radionuclides are uranium and cobalt compounds. Uranium compounds are widely used in the nuclear fuel cycle. They get into the environment mainly with the wastewater of hydrometallurgical plants processing uranium ores and also are components of liquid radioactive waste of nuclear power plants [1]. Pollution by cobalt compounds is possible due 6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The application of IR spectroscopy makes it possible to determine different types of active centers on the surface of the composite. As is known [21], the main active centers of the studied materials will be hydroxyl and carboxyl groups (Fig. 3).…”
Section: Synthesis Of Granular Composites and Study Of Their Porous S...mentioning
confidence: 89%
“…The application of IR spectroscopy makes it possible to determine different types of active centers on the surface of the composite. As is known [21], the main active centers of the studied materials will be hydroxyl and carboxyl groups (Fig. 3).…”
Section: Synthesis Of Granular Composites and Study Of Their Porous S...mentioning
confidence: 89%
“…In our previous publication, we have shown that clay minerals, which are widely used for water treatment [17,18], can be excellent absorbers of MWs, demonstrating high values of maximum heating rate [1]. MW-assisted pyrolysis of cellulose mixed with bentonite resulted in 25 wt.% enhancement of bio-oil.…”
Section: Introductionmentioning
confidence: 94%